Effect of surfactant concentration on textural, morphological and magnetic properties of CoFe2O4 nanoparticles and evaluation of their adsorptive capacity for Pb(II) ions. Issue 10 (December 2015) - Culita, Daniela C.; Simonescu, Claudia Maria; Dragne, Mioara; Stanica, Nicolae; Munteanu, Cornel; Preda, Silviu; Oprea, Ovidiu
Abstract: Mesoporous CoFe2 O4 nanoparticles were synthesized through a simple precipitation method using cetyltrimethylammonium bromide (CTAB) as surfactant. Variation of surfactant concentration has been investigated to synthesize CoFe2 O4 nanoparticles with superior textural properties. The samples were characterized by FTIR, TG/DSC, XRD, SEM, N2 adsorption–desorption technique, and vibrating sample magnetometer (VSM). The obtained results revealed that the surface area and magnetic properties of CoFe2 O4 are significantly influenced by the initial concentration of CTAB. The capacity of the synthesized samples to adsorb lead ions from aqueous solution and the factors affecting the adsorption process, like contact time and pH of the media, were evaluated. The Pb 2+ adsorption followed pseudo-second-order kinetics, and the maximum Pb 2+ adsorption capacity was 32.11 mg g −1 according to the Langmuir isotherm.